UJI EKSPERIMENTAL DAN ANALISIS PERPINDAHAN PANAS PADA SERPENTINE CHANNEL UNTUK PENDINGIN PANEL SURYA MENGGUNAKAN FLUIDA NANO - Amri Abdulah; Dede ardi rajab; Jaenudin; Ina, Ina afriani; Dani, Muhamad; Nur Alam, Deden (Jurnal Teknologika, 2024)
The potential of solar energy in Indonesia is quite large as a renewable energy source, usually called solar panels or photovoltaic (PV) technology as a device capable of converting solar radiation into electrical energy. When solar panels operate, only about 15% of solar radiation is converted into electrical energy, while the rest is converted into heat. The intensity of solar radiation and the temperature of the surrounding air affect the voltage and current produced by solar cells. This condition requires a device that can regulate the temperature state of the solar panel. This study was conducted to overcome the heat problem in solar panels through optimizing the thermal properties of the cooling fluid by adding nano-sized SEM/EDS-tested particles to the W/EG base fluid, which is commonly called nanofluids, then making serpentine channels as a heat exchanger was also carried out. The experimental test process was carried out with a flow rate variation of 1 to 3 LPM and the inlet temperature was kept at 35˚C. The results showed that the highest cooling fluid flow rate was the most optimum condition. The Reynolds number shows that the heat transfer coefficient increases by 1011.72 W/m◦K, 1321.72 W/m◦K, and 2070.39 W/m◦K, respectively. The Nusselt number tends to increase as the Reynolds number of the nanofluid increases. An increase in Nusselt number indicates an increase in heat transfer coefficient, while Reynolds number indicates laminar flow of the coolant. Similarly, the pressure drop increases with increasing flow rate.